The role of insurance to act as al-`Aqilah in paying diyah that is resulting from accidents, an analytical study - Husni, Ahmad Muhammad (Zes Rokman Resources (2131022-P), 2022)
Insurance is the most important contemporary issues and emerging among Muslims, as it bears several concepts that one finds himself to stand with it. The study of legitimacy and practical application must be covered, to see if this issue that have occupied the Muslims for more than sixty years through international and scientific conferences complies with Maqasid Sharia Islamiyah and it foundation. The issue of payment of diyah by the contemporary insurance companies is considered as one of the most important jurisprudence issues emerging at the present time. As the routine among the people when requesting the diyah, to concentrate on the amount of compensation paid by the contemporary insurance companies. Particularly as result of car accidents and what are the alternatives they have provided through these councils when there is no Al-`Aqilah or baitulmal for Muslims and what about the inability of Al-`Aqilah itself to pay diyah due to certain circumstances or the need of the Muslim community to such a type of contracts. Thus, i adopted in this study the inductive and analytical approach to gather the views of fuqaha, researchers, their evidence and arguments on the subject and texts related to it trying to perform fundamental and judicial analysis to suit the contemporary reality and the intent of the Sharia, and to the practical approach which study of the subject in the field and applied study. I concluded the study, that for the commercial companies must be served as Al-`Aqilah in the payment of diyah for the mistaken offender from their insurer, and that does not differentiate between diyah and compensation in terms of the claim and the jurisdiction.